Pengembangan Modul Resiliensi Untuk Mahasiswa Generasi Z - Karunia Sari, Diana; Setyadi, Dendy (Universitas Palangka Raya, 2024)
The purpose of this research is to develop a resilience module product for Generation Z students that is practical and feasible to use to provide information about resilience to students and to determine the feasibility of the resilience module from the responses of Generation Z students in the Guidance and Counseling Study Program of Sanata Dharma University. This research uses the Research and Development method developed by Borg and Gall. This research was modified into 5 stages, namely: research and information gathering, planning, initial product format development, initial product validation, and product revision. This research was assessed by three expert validators, namely material expert validators, media expert validators, and assessed by user validators, namely students. This research produced a module book entitled